The school model in the LOE. Relationships between school model and educational quality - Rul Gargallo, Jesús (Avances en Supervisión Educativa, 2007)
The author analyses the key-factors of school models which provide high-quality effectiveness for the Educational System, as a criterium to judge the school model proposed by the Organic Act of Education.